The Development of Canva-Assisted Problem-Solving Approach Teaching Materials to Improve Students’ Mathematical Communication Ability on Vocational School based on Learning Independence - Amirudin, Neng Hendriawati; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2024)
Mathematical communication ability and learning independence is one of the things that students must have and master in order to achieve competency in learning, especially in learning mathematics. This research has the aim of improving mathematical communication skills and learning independence of class X students of Al-IHSAN Batujajar Vocational School through the development of mathematics teaching materials on sequences and series material using a problem solving approach assisted by the Canva video application. The research method used is the research and development (RnD) Plomp model. The instruments used are teaching material validation tests, mathematical communication skills tests and non-learning independence tests. The validation instruments were given to ICT experts and material experts. As for the ability and independence tests given to class X students of SMK Al-IHSAN. From the results of the study it was found that the teaching materials developed showed very valid results based on the results of ICT expert and material expert assessment and based on the results of student assessments it was found that the teaching materials were very feasible to use and received very practical criteria. In addition, the application of the problem solving approach in learning can improve students' mathematical communication skills and also student learning independence in terms of the results of post-test data analysis.